Icon of the Holy Mandylion and representation of multi-layered visual identity of Božidar Vuković - Borozan Igor (Zograf, 2015)
It was in the monastery of Saint Francis in Venice in the year 1520 when Božidar Vuković purchased the icon of the Holy Mandylion. By that particular acquisition, this prominent publisher originating from Zeta has visualized his new position in the sixteenth century Venice. The multi-layered identity of Božidar Vuković was manifested by the subsequent inclusion of the noble coat of arms of the House of Vuković on the back of the icon. By the use of verbal and visual language the artificial initiation of Božidar Vuković within the distinguished members of Venetian society has been confirmed. [Projekat Ministarstva nauke Republike Srbije, br. 177001: Predstave identiteta u verbalno-vizuelnoj kulturi novog doba]